The cross and creation in Christian liturgy and art - Irvine, Christopher (Alcuin Club collections, 2013)
The book gives an account of various movements in art and their relation to the visual and in churches and in liturgy, for example the Franciscan movement, different approaches to the crucifixion, the restoration of creation. It recovers the links between the cross and creation, and relates the baptismal covenant to a commitment to care for creation. Includes a 4-page colour plate section